Cutaneous manifestations of anti retroviral therapy used for post-exposure prophylaxis - Jani, Chinmay T.; Malhotra, Supriya D.; Patel, Pankaj R. (International Journal of Basic & Clinical Pharmacology, 2018)
Health care workers are at increased risk of needle stick injuries. Blood borne diseases that could be transmitted by such an injury include HIV, Hepatitis B, HCV and many others. Post exposure prophylaxis should be immediately started within 72 hours and should be continued for 28 days. Currently two Nucleoside Reverse Transcriptase Inhibitors (NRTIs) are given along with one NNRTI (Non- Nucleoside reverse Transcriptase Inhibitor) including Efavirenz or Nevirapine. Multiple adverse effects have been reported with all the Anti- Retroviral Therapies including various cutaneous manifestations. A 22-year-old intern doctor studying in tertiary hospital of Ahmedabad had a needle stick injury with a needle contaminated with blood of HIV positive patient. Post Exposure prophylaxis was started within 72 hours consisting of fixed dose regimen of Tenofovir disprodoxil sulphate, Efavirenz and lamivudine. He was started with the drug within 2 hours and was prescribed one drug per day for next 27 days. On 22nd day he started having rash on his body which started on palms and soles. On 23rd day he saw severe facial edema along with edema on lips and rash spreading to other parts of the body. He was diagnosed with Hypersensitivity reaction and angioedema due to ART drug therapy. He was instructed to stop ART medications and was given antihistaminic for the symptoms. Patient's angioedema was relieved in 2-3 days and rash disappeared after 4-5 days. As he had already finished 23 days of therapy he was instructed to discontinue the drugs. No recurrence of rash or angioedema was noted. This case points out the severity of side effects in the normal healthy people taking ART as Post Exposure Prophylaxis. Apart from cutaneous manifestations, angioedema is a very grievous condition which doctors should always have lower threshold for diagnosis. Early diagnosis can prevent further complications. ART drugs have many complications and these patients should have intensive regular monitoring while on treatment. Also, proper education is required for needle cut injuries in health care workers.